2015
DOI: 10.5603/kp.a2014.0230
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological pattern of myocardial infarction and modelling risk factors relevant to in-hospital mortality: the first results from the Iranian Myocardial Infarction Registry

Abstract: STEMI, lack of thrombolytic therapy, age of over 84 years, and ventricular tachycardia have the greatest effect on in-hospital mortality in MI patients. The results of this study are helpful in planning for monitoring and promotion of healthcare of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…They demonstrated a statistically significant dependency for sinus rhythm, atrial fibrillation, ventricular tachycardia atrioventricular blocks. As a result of their research, Ahmadi et al [14] included right His bundle branch block and ventricular tachycardia in the group of myocardial infarction risk factors. Our research into 12-lead ECG results found sinus rhythm OR=2.860 (CI 95%) and additional ventricular beats OR= 9.120 (CI 95%) to be significant predictors of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a statistically significant dependency for sinus rhythm, atrial fibrillation, ventricular tachycardia atrioventricular blocks. As a result of their research, Ahmadi et al [14] included right His bundle branch block and ventricular tachycardia in the group of myocardial infarction risk factors. Our research into 12-lead ECG results found sinus rhythm OR=2.860 (CI 95%) and additional ventricular beats OR= 9.120 (CI 95%) to be significant predictors of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mortality rate of patients was lower than those of some previous studies in Iran and higher than those of some others performed worldwide. An epidemiologic study on 20,750 patients with acute MI reported a general mortality rate of 12.1%, while about 85% of deaths were related to patients with STEMI [26]. Another study also reported a mortality rate of 13.2% for MI, with significantly worse outcomes in patients with STEMI [27].The mortality rates reported in these studies, although similar to that of the thrombolytic group, cannot be compared with those of the current study, since they did not report the rates based on the type of MI (STEMI vs. non-STEMI) or the treatments received.…”
Section: Discussionmentioning
confidence: 99%
“…Donyavi et al, reported a mortality rate of 24.6% after acute MI in Iranian patients [28], which was higher than the mortality rates of both groups in the present study, although they did not separate the rates based on the type of disease. An important findings of these studies indicated that the socio-demographic characteristics of patients, type of MI, and the concomitant diseases played a fundamental role in the mortality rate [26][27][28], which could also attribute to the difference in the reported mortality rates. One of the limitations of the present study was the nonrandom inclusion of patients into the study and selection of patients from one center, which decreased the generalizability of the results, although the study site was a tertiary center in the city center with high patient load.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, among the smoking female, the age of death occurs about 14.5 years earlier and in the case of men, smokers die 13.2 years earlier thannonsmokers [13,14]. It is estimated that smoking is responsible for about 10% of all cardiovascular deaths [15].Cessation of smoking is the most important intervention in preventive cardiology.After an acute coronary event, quitting smoking reduces cardiovascular mortality by 36% [15].…”
Section: Smokingmentioning
confidence: 99%